Persepsi Remaja Terhadap Cyberbullying - Negolara Dokubani, Kireina; Hendriani, Wiwin (Jurnal Syntax Fusion, 2023)
up to 679 cases. Cyberbullying occurs mostly among teenagers. Various efforts have also been made to prevent and overcome cyberbullying. But from the various efforts that have been made, cyberbullying behavior still continues to occur today. Cyberbullying also occurs due to technological developments that are increasingly uncontrolled. So based on the description above, the researcher wants to know how adolescents view cyberbullying based on the concept of proper perception. This research is qualitative research with a case study approach. Participants in this study were adolescents aged 15-18 years and actively using social media at least 4 hours a day. Data collection was carried out by distributing questionnaires. This research uses Braun and Clarke thematic analysis. The results of this study found that the subjects assessed the behavior of vilifying, making fun of, insinuating, and spreading hoaxes about someone is what is perceived as cyberbullying behavior. In addition, subjects also have different perceptions of cyberbullying which are divided into three subject groups. Perpetrator subjects tend to have the perception that cyberbullying is fun, often justified as social sanctions, and common and understandable. The bystander subjects had interesting answers. Subjects have the perception that cyberbullying is understandable if it is intended to retaliate. So it can be said that the perpetrator and bystander subjects do not have understanding discipline. In contrast to the perception possessed by the victim Subject.